La inestabilidad laboral de los servidores públicos ecuatorianos a consecuencia del decreto ejecutivo 813. - Walter Pinos, Oswaldo (2015)
Conducting this research the enfocamos towards the violation of labor rights of public servants , which are covered within our Constitution of the Republic of Ecuador in Article 229 on the rights of public servants especially in the second paragraph where first part states: " . rights of public servants are INALIENABLE " But the Executive Decree No. 813 contravene and violates this right set out in numbered article ... (108.1 ) of the General Regulations of the Law organic Public Service, which states: . " Cessation of purchasing functions waivers with damages - State Institutions may establish plans COMPULSORY purchase compensation as determined with the letter k ) of Article 47 of the duly LOSEP budgeted under restructuring, optimization or rationalization of the same. " We also reviewed the provisions of Article 47 of the LOSEP in its literal k ) which states: " Purchase waiver for compensation" , says it is not mandatory, what is meant is that if the server wants to sell his resignation with compensation is something that cannot be forced , by what right to work in an institution is indispensable ; despite that there have been several untimely dismissals in different state institutions , without the right to defense only because it supposedly would not work and beating their users, but the question we ask is what evidence were shown to have been applied this decree ? For what hit you had no right time to do anything and everything was done that is not entitled to the defense and to due process , for this reason many of those affected psychologically demotivated as they were above our Constitution and the law, although clearly established in Article 424 and 425 on the Supremacy of the Constitution were ignored here , so where the rights and guarantees are supporting and protecting the Constitution of the Republic in each of the citizens of this country and also analyze this problem not only injures the public servant but also entire families who depend on work of the household head , to survive, though perhaps in a number of cases have received compensation , but is not the same to keep working unless they had not really wanted to work where they could benefit from the waiver formally presented it to the Organic law of Public Servants , or turn it really is proven that the poor service of public servants , but his right basis and justification defense and which perform the due process that the Constitution guarantees in Article 76 and not from one day to the other with a notice , in which you state that charges cease permanently , violating labor rights of public servants , for which in our research and our analysis suggest possible solutions , where the Executive to repeal Decree 813